2022
DOI: 10.1186/s13054-022-03904-6
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy timing and clinical outcomes in ventilated COVID-19 patients: a systematic review and meta-analysis

Abstract: Background The association of tracheostomy timing and clinical outcomes in ventilated COVID-19 patients remains controversial. We performed a meta-analysis to evaluate the impact of early tracheostomy compared to late tracheostomy on COVID-19 patients’ outcomes. Methods We searched Medline, Embase, Cochrane, and Scopus database, along with medRxiv, bioRxiv, and Research Square, from December 1, 2019, to August 24, 2021. Early tracheostomy was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 65 publications
2
16
0
6
Order By: Relevance
“…Considering 47 studies for the outcome mortality, our results showed a pooled tracheostomy mortality in COVID-19 of 21.6% (95%CI=18.1-25.0), similarly to that previously reported by Ferro and co-workers 13 of 19.2% (95%CI=15.2-23.6) including 37 studies, and Ji and co-workers including 14 studies 14 , but higher than that reported by Benito and co-workers 12 of 13.1% (95%CI=8.5-18.4) including 14 studies. Ferro and co-workers reported no differences in cumulative mortality between early and late tracheostomy (RR=1.6, 95%CI=0.2-11.8) and surgical vs. percutaneous tracheostomy (RR=2.0 95%CI=0.2-20.4) 13 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Considering 47 studies for the outcome mortality, our results showed a pooled tracheostomy mortality in COVID-19 of 21.6% (95%CI=18.1-25.0), similarly to that previously reported by Ferro and co-workers 13 of 19.2% (95%CI=15.2-23.6) including 37 studies, and Ji and co-workers including 14 studies 14 , but higher than that reported by Benito and co-workers 12 of 13.1% (95%CI=8.5-18.4) including 14 studies. Ferro and co-workers reported no differences in cumulative mortality between early and late tracheostomy (RR=1.6, 95%CI=0.2-11.8) and surgical vs. percutaneous tracheostomy (RR=2.0 95%CI=0.2-20.4) 13 .…”
Section: Discussionsupporting
confidence: 89%
“…To the best of our knowledge, this is the first systematic review, meta-analysis and meta-regression in COVID-19 tracheostomized critically ill patients which reports the associations between outcomes and moderators as sources of between-study heterogeneity accounting for the effects of study duration (partial accounting for time-varying associations) and study start date (hospital strain), as well as the comparison between early vs. late at different cut-offs, and technique (surgical vs. percutaneous tracheostomy) for several outcomes, including mortality, hospital- and ICU-LOS, decannulation, duration of MV, and complications. Previous meta-analyses reported the comparison between such sub-groups of patients only for a few outcomes 12 , 13 , 14 , 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis concerning the optimal timing of tracheotomy in COVID-19 patients concluded that early tracheotomy, defined as 14 days from intubation or less, implied reduced number of days in MV and days spent at the ICU compared to late tracheotomy (15 days after intubation or later) [ 20 ]. No RCTs were, however, available for this meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Tracheostomy is considered an effective alternative to invasive MV via tracheal tube since it helps to reduce dead-space ventilation and decreases airway resistance and the risk of aspiration, as well as the need for sedation, facilitating weaning from a ventilator [ 18 ]. During the COVID-19 pandemic, there was incomplete evidence that early tracheostomy is preferable to late tracheostomy, and there is no compelling evidence that percutaneous is preferable to surgical (open) [ 5 , 19 , 20 , 21 ]. Consequently, the appropriate MV strategy for COVID-19 respiratory failure is still disputed.…”
Section: Introductionmentioning
confidence: 99%